Kelayakan Bisnis Peningkatan Produksi Lalat Black Soldier Fly Pada PT Biomagg Indonesia - Rizano, Desvand Theola Da; Rifin, Amzul; Suprehatin (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
The business development of BSF insect have problems especially in maggot production. The purpose of this study is analyze the feasibility of best alternatives business strategy to increasing production of black soldier fly. This research was conducted in December 2019-February 2020. The type of data used is primary data of financial and non-financial aspects. Data collected by quantitative method through interviews with Mr. Aminudi as CEO of Biomagg Indonesia Ltd and Prof.Dewi Astuti as an expert of BSF flies. The business feasibility analysis in this study includes aspects of financial visibility (NPV, IRR, profitability index and payback period) and non-financial aspects (legal, technic and operating aspects, management, socioeconomic and nature). The analysis shows that all scenario was worth from non-financial and financial feasibility aspects The problem of deficiencies in supply of organic waste can be solved by running scenario two which Biomagg Indonesia Ltd buy organic waste from traditional market and Islamic school. the financial feasibility of third scenario was worthy to run because it has the best NPV , IRR , profitability index and payback period . the logistic problem can be resolved by running the first scenario to move cages close to the source of organic waste was in urban areas. Biomagg Indonesia Ltd in first scenario made cooperation with Institute of Research and Development Ornamental Fish Culture to built the cage. Biomagg Indonesia Ltd does not need cost to built it. Keywords: business feasibility analysis, black soldier fly, food waste, maggot